Study of genotype x environment interaction for forage yield in oat (Avena sativa L.) with joint linear regression analysis and AMMI analysis - Acciaresi, Horacio Abel (1997)
Improvement of forage yield in oat (Avena sativa L.) depends on thorough understanding of the influences of genotype, environment and the genotype x environment interaction (G X E). The objetive of this study was to analyze G X E interaction in oat for biomass forage yield according two different models, joint linear regression analysis (JRA) and AMMI analysis. Twelve genotypes were grown in different environments during three years (1993-94-95) at the locations of La Dulce and La Plata, Buenos Aires Province, Argentina. The forage yield (dry matter yield Kg/ha) was determined at 60, 100 days after emergence and at ripening. Heterogeneity of regression in JRA was nonsignificant. Interaction sume of square accounted for by heterogeneity of regression were 12.08 % (three years mean). In contrast, the first principal component axis in AMMI was highly significant (P<.001). This first axis accounted for by 68.46 % of interaction SS (three years mean). The AMMI model was found tobe more effective than JRA analysis in accounting for GXE interaction under low environmental diversity The use of AMMI is recommended for the study of GXE effects in the oat breeding for forage yield.